1990
DOI: 10.1002/aic.690361011
|View full text |Cite
|
Sign up to set email alerts
|

Mercury‐sensitized photochemical vapor deposition of amorphous silicon

Abstract: A reaction engineering model has been developed to describe the mercury-sensitized photochemical vapor deposition of hydrogenated amorphous silicon (a-Si:H) semiconductor thin films. Model equations governing the gas-phase generation, transport, and surface reactions of SiH, and H film precursor radicals are solved to predict film growth rate and bonded hydrogen content. Behavior of the model has been studied as a function of deposition conditions (pressure, temperature, feed composition, and flow rates) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Details about this method and growth parameters are given elsewhere. 5 A semitransparent palladium contact was evaporated onto the samples to provide a Schottky barrier for both the junction modulated photocurrent and junction capacitance measurements. We have demonstrated that modulated photocurrent spectroscopy is a powerful technique to determine the energy distribution of the relaxed DO sub-band in a-Si:H. 3 Fast light emitting diodes with peak fluxes at different wavelengths were used as sinusoidal excitation sources over frequency range from 5Hz to 100kHz.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Details about this method and growth parameters are given elsewhere. 5 A semitransparent palladium contact was evaporated onto the samples to provide a Schottky barrier for both the junction modulated photocurrent and junction capacitance measurements. We have demonstrated that modulated photocurrent spectroscopy is a powerful technique to determine the energy distribution of the relaxed DO sub-band in a-Si:H. 3 Fast light emitting diodes with peak fluxes at different wavelengths were used as sinusoidal excitation sources over frequency range from 5Hz to 100kHz.…”
Section: Experimental Techniquesmentioning
confidence: 99%